The impact of the Financing Policy for Developmental Social Welfare Services (1999) on service providers in Tembisa, Gauteng Province - Lombard, A. (Antoinette) (University of Pretoria, 2013)
Dissertation (MSD (Social Policy))--University of Pretoria, 2006.